Interest of [18F]fluorodeoxyglucose positron emission tomography/computed tomography for the diagnosis of relapse in patients with spinal infection: a prospective study. (May 2016) - Dauchy, F.-A.; Dutertre, A.; Lawson-Ayayi, S.; de Clermont-Gallerande, H.; Fournier, C.; Zanotti-Fregonara, P.; Dutronc, H.; Vital, J.-M.; Dupon, M.; Fernandez, P.
Abstract: Relapse after treatment of a spinal infection is infrequent and difficult to diagnose. The aim of this study was to assess the diagnostic performance of [ 18 F]fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in this setting. Thirty patients (21 men, nine women; median age 61.2 years) with a suspected spinal infection relapse were prospectively included between March 2010 and June 2013. The initial diagnosis of spinal infection was confirmed by positive bacterial cultures. The patients underwent [ 18 F]FDG PET/CT and magnetic resonance imaging (MRI) 1 month after antibiotic treatment interruption. PET/CT data were interpreted both visually and semi-quantitatively (SUVmax ). The patients were followed for ≥12 months and the final diagnosis of relapse was based on new microbiological cultures. Seven patients relapsed during follow up. Sensitivity, specificity, positive predictive value and negative predictive value were 66.6%, 61.9%, 33.3% and 86.6%, respectively for MRI and 85.7, 82.6, 60.0 and 95.0 for PET/CT. Although these values were higher for PET/CT than for MRI, the difference was not statistically significant (p=0.3). [ 18 F]FDG PET/CT may be useful for diagnosing a relapse of spinal infections, in particular if metallic implants limit the performance of MRI.